Association Between Promoter Polymorphisms of IL-1Β, IL-4 and IL-6 Genes and a Viral Load Infected Women with Human Papillomavirus - AH Albosale; EV Mashkina (JRI, 2021)
Background: The purpose of this study was to investigate the association between IL-4 -589C>T, IL-6 -174G>C, IL-1β -31T>C and IL-1β -511C>T genes polymorphism with high concentrations of human papillomavirus (HPV), and the influence of gene-gene interactions on persistent human papillomavirus infection. Methods: In this study, 101 infected women with high HPV viral load and 93 healthy women were involved in a case-control study. Genotyping of SNPs for IL-4 -589C>T, IL-6 -174G>C, IL-1β -31T>C and IL-1β -511C>T genes was carried out by allele-specific PCR. Quantitative analysis of HPV-DNA was performed by Amplisens HPV HCR genotype-titer software. Gene-gene interactions were analyzed using multifactor dimensionality reduction (MDR) algorithm. Haplotype interactions were analyzed by HaploView 4.2 tool. Results: The study of single individual SNPs in promoters of IL-4 -589C>T, IL-6-174G>C and IL-1β -31T>C genes did not reveal statistically significant difference in genotypes and allele frequencies among women with high HPV viral load and control group. The frequency of -511T allele and TT genotype of the IL-1β gene in case group was significantly higher than the one in control group (OR=1.71, p=0.012 and OR=2.02, p=0.046, respectively). Haplotype analysis revealed that -511C/-31T haplotype for IL-1β gene is significantly less common among women with high HPV viral load  (p=0.018). Conclusion: The haplotype -511C/-31T for IL-1β gene is associated with a protective effect against increasing HPV viral load. The frequencies of -511T allele and -511TT genotype of the IL-1β -511C>T were significantly higher among women with HPV in comparison to control group.